Dynamic Functional Brain Connectivity for Face Perception - Yang, Yuan; Qiu, Yihong; Schouten, Alfred C. (Frontiers in Human Neuroscience, 2015)
Face perception is mediated by a distributed brain network comprised of the core system at occipito-temporal areas and the extended system at other relevant brain areas involving bilateral hemispheres. In this study we explored how the brain connectivity changes over the time for face-sensitive processing. We investigated the dynamic functional connectivity in face perception by analyzing time-dependent EEG phase synchronization in four different frequency bands: theta (4-7 Hz), alpha (8-14 Hz), beta (15-24 Hz) and gamma (25-45 Hz) bands in the early stages of face processing from 30 ms to 300 ms. High-density EEG were recorded from subjects who were passively viewing faces, buildings and chairs. The dynamic connectivity within the core system and between the extended system were investigated. Significant differences between faces and non-faces mainly appear in theta band connectivity: 1) at the time segment of 90-120 ms between parietal area and occipito-temporal area in the right hemisphere, and 2) at the time segment of 150-180 ms between bilateral occipito-temporal areas. These results indicate 1) the importance of theta-band connectivity in the face-sensitive processing, and 2) that different parts of network are involved for the initial stage of face categorization and the stage of face structural encoding.